A wrinkle in time and related readings. (Evanston, IL : McDougal Littell, 2002)
Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who has disappeared while engaged in secret work for the government. Includes eight related readings.
A wrinkle in time / Madeleine L'Engle --Odd jobs / Judith Gorog -- Reversible / Octavio Paz -- Behind bars / Fadwa Tuqan -- The dark princess / Richard Kennedy -- The sparrow / Ivan Turgenev -- Colony / Rick Wernli.
Keywords: Science fiction; Science fiction; Science fiction